3
$\begingroup$

Let $C=\{(-a, a): a \in \mathbb{R}\}$ and $F=\sigma(C)$.

Prove that $F=\mathcal{B}(\mathbb{R})\cap\{A\subseteq\mathbb{R}: A=-A\}$.

I don't have problems in proving $F\subseteq \mathcal{B}(\mathbb{R})\cap\{A\subseteq\mathbb{R}: A=-A\}$, I'd like a confirm for the other inclusion.

Let $F^+=\{A \cap [0,+\infty): A \in F\}$, then $F^+=\mathcal{B}[0,+\infty)$:

$F\subseteq \mathcal{B}(\mathbb{R}) $ and $[0,+\infty) \in \mathcal{B}(\mathbb{R})$ imply $F^+\subseteq \mathcal{B}[0,+\infty)$;

$\forall a,b\in[0,+\infty)$ we have $(a,b)=[0,b) \cap \cup_n[a+n^{-1},+\infty) \in F^+$, but $\mathcal{B}[0,+\infty) $ is generated by those intervals so $F^+\supseteq \mathcal{B}[0,+\infty)$; hence the equality.

Now take $B\in \mathcal{B}(\mathbb{R})\cap\{A\subseteq\mathbb{R}: A=-A\}$; we have $B\cap[0,+\infty)\in \mathcal{B}[0,+\infty)=F^+$. So there exists $A\in F$ such that $A\cap[0,+\infty)=B\cap[0,+\infty) $ which means that A and B have the same positive elements, and since they are equals to their opposites they also have the same negative elements. Therefore $B=A\in F$, from which $$F\supseteq \mathcal{B}(\mathbb{R})\cap\{A\subseteq\mathbb{R}: A=-A\}$$

$\endgroup$
  • $\begingroup$ With $-A$ I mean $\{-a: a \in A \}$. For example, $(-a, a)= -(-a, a)$. $\endgroup$ – user May 10 at 14:15
  • 1
    $\begingroup$ This seems correct to me. EDIT: This proof is actually very elegant $\endgroup$ – Maximilian Janisch May 16 at 19:24
  • $\begingroup$ I am much too tired right now to check the details but this is exactly the right idea. $\endgroup$ – DanielWainfleet May 18 at 4:57
  • $\begingroup$ I wonder if it would be possible to use that $\Bbb R$ and $(0,a)$ are homeomorphic (e.g. by $g(x)= a\cdot e^x/(1+e^x)$) $\endgroup$ – Mirko May 23 at 2:38
1
+50
$\begingroup$

I go to prove: $\mathcal{B}(\mathbb{R}) \cap \{ A\subseteq \mathbb{R} \mid A=-A \} \subseteq \mathcal{F}$.

Let $\mathcal{B}=\mathcal{B}(\mathbb{R})$, $\mathcal{B}_{1}=\mathcal{B}([0,\infty))$, $\mathcal{G}=\{A\subseteq\mathbb{R}\mid A=-A\}$, $\mathcal{C}=\{(-a,a)\mid a>0\}$, and $\mathcal{F}=\sigma(\mathcal{C})$ on $\mathbb{R}$. Note that $\mathcal{B}$ and $\mathcal{G}$ are $\sigma$-algebras on $\mathbb{R}$ while $\mathcal{B}_{1}$ is an $\sigma$-algebra on $[0,\infty)$. Define $f:\mathbb{R}\rightarrow[0,\infty)$ by $f(x)=|x|$. Let $\mathcal{D}=\{[0,a)\mid a>0\}$. It is well-known that $\mathcal{D}$ is a generator for $\mathcal{\mathcal{B}}_{1}$ (in the sense that $\sigma(\mathcal{D})=\mathcal{B}_{1}$ on $[0,\infty)$). Clearly, for each $A\in\mathcal{D}$, $f^{-1}(A)\in\mathcal{B}\cap\mathcal{G}$ because $f^{-1}\left([0,a)\right)=(-a,a)$. Therefore $f$ is $(\mathcal{B}\cap\mathcal{G})/\mathcal{B}_{1}$-measurable. Moreover, we have, \begin{eqnarray*} f^{-1}(\mathcal{B}_{1}) & = & f^{-1}(\sigma(\mathcal{D}))\\ & = & \sigma(f^{-1}(\mathcal{D}))\\ & = & \sigma(\mathcal{C})\\ & = & \mathcal{F}. \end{eqnarray*} Given $A\in\mathcal{B}\cap\mathcal{G}$, we define $B=[0,\infty)\cap A$. Note that $A\in\mathcal{B}\Rightarrow B\in\mathcal{B}_{1}$. Therefore $f^{-1}(B)\in\mathcal{F}$. However, $f^{-1}(B)=B\cup(-B)=A$. This shows that $\mathcal{B}\cap\mathcal{G}\subseteq\mathcal{F}$. (It is elementary and routine to check that $B\cup(-B)=A$ by observing that $A=-A$. For, $B\subseteq A$ by definition. Let $x\in-B$, then $-x\in B\subseteq A$, and hence $x\in-A=A$. Therefore $-B\subseteq A$ and hence $B\cup(-B)\subseteq A$. To show the reverse inclusion, let $x\in A$. If $x\geq0$, then $x\in B$ by the very definition. Suppose that $x<0$, then $-x>0$. Since $A=-A$, we have $-x\in A$. Therefore $-x\in B$ and hence $x\in-B$. This shows that $A\subseteq B\cup(-B)$.)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.